ANALISIS STRUKTUR DAN PERTUMBUHAN SERTA PENYERAPAN TENAGA KERJA PADA SEKTOR PEREKONOMIAN DI KABUPATEN OGAN KOMERING ULU (JASEP, 2015)
This research aims at analyzing the economic structure in Ogan Ogan Ulu during the years 2008-2012 and the shifting role of economic sectors, especially in labor absorption and the growth and the contribution of its output. Employment in the agricultural sector is greater than the industrial sector and increased during 2008-2012. This study used an analytical tool LQ (Location Quotien), Tipology Klassen and Shift-share. LQ analysis results showed that the services sector and industry are leading sectors with LQ value of 1.87 and 1.10 in 2012. Klassen Typologi analysis results show that the industry and services sector is a sector that is advancing and growing fast. Shift-Share analysis results Overall labor sector in OKU District experienced an absolute value or increase in the economic performance of the labor force is relatively faster than petumbuhan similar sectors in the economy of the province.